Effect of sequentially adsorbed multilayers, citric acid(CA)-PEI-CA-PEI and PEI-CA-PEI-CA, on the surface chemistry and rheology of spherical α-alumina suspensions. Issue 8 (3rd August 2019) - Zhang, Wei; Leong, Yee-Kwong; Sun, Chunbao; Fan, Hong; Zhang, Xianwei
Abstract: The yield stress and zeta potential of washed spherical α-Al2 O3 suspensions with two to four layers of critic acid(CA) and polyethyleneimine(PEI_Mw1.8and 70 kDa) adsorbed sequentially were characterized. With CA adsorbed as the first layer, pHξ=0 was shifted to a lower pH and the maximum yield stress (τymax ) was reduced. With PEI adsorbed as the first layer, the pHξ=0 was moved slightly higher. With the introduction of the second layer, the CA/PEI additive was formed which functioned as a bridging agent. The pH range of yield stress was broadened significantly and increased with the number of layers. This pH ranged from 2.5 to 11. The CA/PEI multilayer additive loses its positive charge at pH >11. There was less adsorption in layer3 and layer4 when lower Mw PEI is applied to the suspension. The CA/PEI multilayer additive formed by PEI of Mw 70000 and CA was larger in size than that formed by PEI of Mw 1800 and CA. Lower Mw PEI produced a stronger flocculated network or higher τymax suspension due to a higher concentration of multilayer additive. CA/PEI multilayer additive was participating in bridging and particle bridging interaction was not affected by the adsorption order of CA and PEI.GRAPHICAL ABSTRACT